Maturity of the accountability process of social health organisations: evidence from Sao Paulo in Brazil. Issue 7 (2nd October 2020) - Figueiredo, Raquel Ferreira Leite; Gomes, Matheus da Costa; Fregonesi, Mariana Simões Ferraz do Amaral; Bonacim, Carlos Alberto Grespan
ABSTRACT: This article evaluates the maturity of the accountability process of social health organisations (SHOs) in the state of Sao Paulo, Brazil, reviewing financial information disclosed by 33 SHOs in 2017 using quantitative analysis. It finds that 16 SHOs did not have accountability maturity, while nine presented low maturity and eight had high maturity. The poor level of maturity through the disclosure of financial information demonstrates the organisations' perceptions of the relative unimportance of transparency in this sector, providing scope for irregularities and non-compliance with management contracts.